Strongly damped semilinear equations. (1995) - Bahuguna, D.
Abstract : A class of strongly damped semilinear equations is studied by using the theory of analytic semigroups. Conditions (on the nonlinear forcing term) are given under which the existence and uniqueness of local and global classical solutions are ensured.